Power and the Vote : Elections and Electricity in the Developing World - Min, Brian (Cambridge : Cambridge University Press, 2015)
How do developing states decide who gets access to public goods like electricity, water, and education? Power and the Vote breaks new ground by showing that the provision of seemingly universal public goods is intricately shaped by electoral priorities. In doing so, this book introduces new methods using high-resolution satellite imagery to study the distribution of electricity across and within the developing world. Combining cross-national evidence with detailed sub-national analysis and village-level data from India, Power and the Vote affirms the power of electoral incentives in shaping the distribution of public goods and challenges the view that democracy is a luxury of the rich with little relevance to the world's poor.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).